Ultrastructural analysis of submacular choriocapillaris and its transport systems in AMD and aged control eyes. (April 2019) - Grebe, Rhonda; Mughal, Irum; Bryden, William; McLeod, Scott; Edwards, Malia; Hageman, Gregory S.; Lutty, Gerard
Abstract: The choriocapillaris is the source of nutrients and oxygen for photoreceptors, which consume more oxygen per gram of tissue than any other cell in the body. The purpose of this study was to evaluate and compare the ultrastructure of the choriocapillaris and its transport systems in patients with and without age-related macular degeneration (AMD). Ultrastructural changes were also evaluated in subjects that were homozygous for polymorphisms in high risk CFH alleles (Pure 1) only or homozygous only for high risk ARMS2/HTRA1 (Pure 10) alleles. Tissue samples were obtained from the macular region of forty male (n = 24) and female (n = 16) donor eyes and prepared for ultrastructural studies with transmission electron microscopy (TEM). The average age of the aged donors was 74 ± 7.2 (n = 30) and the young donors 31.7 ± 11.25 (n = 10). There was no significant difference in average ages between the adult groups. TEM images of the capillaries in the choriocapillaris (CC) were taken at 4, 000X and 25, 000X and used to measure the area of endothelial cell somas, the number of fenestrations, and area of caveolae within the endothelial cells per length of Bruchs membrane (BrMb). The Student t-test and Wilcoxon sum rank test were used to determine significant differences. There was no significant difference between young subjects and aged controls in any of the morphological criteria assessed. There was a significant decrease in the number of fenestrations/mm of BrMb in atrophic areas of GA eyes (p = 0.007) when compared with aged control eyes. A significant increase was found in the caveolae area as a percent of the endothelial cell soma of capillaries from GA subjects as compared with the controls (p = 0.03). Loss of capillary segments in choriocapillaris was also evident, especially in areas of geographic atrophy and CNV. In eyes from patients with sequence variations, the capillary endothelial cells often appeared degenerative and exhibited atypical fenestrations and pericytes covering the blood vessels. Subjects that were homozygous for polymorphisms in high risk CFH alleles only had more fenestrations/mm of BrMb than subjects that were homozygous only for high risk ARMS2/HTRA1 alleles (p = 0.04), while the latter had greater caveolae area/endothelial cell area than the former (p = 0.007). This study demonstrated an attenuation of CC and a significant decline in the two major transport systems in CC endothelial cells in AMD. This may contribute to drusen deposition, nutrient transport, and vision loss in AMD subjects. Highlights: Choriocapillaris is the source of nutrients and oxygen for photoreceptors and RPE. No difference in the TEM criteria evaluated between young and old controls. Significant reduction in the number of fenestrations in geographic atrophy (GA). The percentage of endothelial cell area that was caveolae was increased in GA. There was attenuation of CC and dysfunction in its transport systems in AMD.